(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This article examines the ethos of American President Donald Trump in the inaugural speech, which he delivered on January 20, 2025, in the United States of America upon his election victory for the second term of presidential office. Indeed, it treats his speech as a text of rhetorical artifact. Thus, this study focuses on how Trump’s strategy of self-portrayal operates rhetorically to gain the confidence of his audience, especially the people of America. The paper applies the ethos as the analytical tool to discuss how Trump evokes the dominant values of nation-building, patriotism, and economic resurgence to establish himself as a credible and authoritative rhetor. Moreover, the paper aims to study the strategy of ethos-building that Trump deploys in his speech to persuade his audience to believe in the truthfulness of his argument and judgment. The study highlights that the core objective of Trump’s speech is to warrant his audience’s unanimity and consensus by focusing on what the American people missed in the past and how they will regain their lost justice, dignity, and sovereignty under the new administration. The findings of the study show that the rhetor evokes himself as an exemplar to underscore the idea that a new beginning is awaiting the people of America. The implication of the study reveals that the character of a person is crucial in instigating people to espouse certain values and beliefs at the expense of some others.